Positive electrode active material and aqueous battery

By using composite oxides with specific crystal structures and compositions as the positive electrode active substances in the water-based battery, the problem of insufficient discharge capacity of the water-based battery in the potassium phosphate aqueous electrolyte in the prior art is solved, and efficient charge compensation and discharge performance are achieved.

CN119764433APending Publication Date: 2025-04-04TOYOTA JIDOSHA KK +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411357514.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-09-18
Filing Date
2024-09-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art is difficult to provide efficient positive electrode active substances suitable for aqueous batteries containing water electrolytes containing potassium polyphosphate, and there are shortcomings in improving discharge capacity.

Method used

A composite oxide with a monoclinic crystal structure belonging to the spatial group C2/m is used as the positive electrode active material, and the specific composition formula is AxMn1-yBiyO2·zH2O, where A is one or both of Na and K, 0

Benefits of technology

With this structure and composition of the positive electrode active material, the discharge capacity of the aqueous battery can be significantly improved, and charge compensation ions can be effectively absorbed and discharged in the aqueous electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764433A_ABST
    Figure CN119764433A_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material and an aqueous battery. The positive electrode active material for an aqueous battery disclosed in the present invention has a monoclinic crystal structure belonging to the space group C2 / m and has a composition formula: x Mn 1‑y Bi y A composition represented by O2·zH2O (A: one or both of Na and K, 0<x<1, 0<y<1, 0<z<2).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application discloses a positive electrode active material and an aqueous battery. Background Art

[0002] In International Publication No. 2020 / 237386, as a positive electrode material for a non-aqueous potassium ion battery, a composition composed of K x M y Mn 1-y Layered potassium metal oxide represented by O2 (M: Co, Fe, Ni, Ti, Cr, V, Cu, Zr, Sb or a combination thereof). Summary of the invention

[0003] There is a need for new positive electrode active materials that can be used in aqueous batteries having an aqueous electrolyte containing potassium polyphosphate.

[0004] The present application discloses the following multiple solutions as means for solving the above-mentioned problems.

[0005] <Option 1>

[0006] The positive electrode active material has a monoclinic crystal structure belonging to the space group C2 / m and has a composition formula: x Mn 1-y Bi y A composition represented by O2·zH2O, wherein A is one or both of Na and K, 0<x<1, 0<y<1, 0<z<2, and the positive electrode active material is used for an aqueous battery having an aqueous electrolyte containing water and potassium polyphosphate dissolved in the water.

[0007] <Option 2>

[0008] An aqueous battery comprising a positive electrode active material layer, an aqueous electrolyte, and a negative electrode active material layer, wherein the positive electrode active material layer comprises the positive electrode active material according to Scheme 1, and the aqueous electrolyte comprises water and potassium polyphosphate dissolved in the water.

[0009] <Option 3>

[0010] The aqueous battery according to claim 2, wherein the aqueous electrolyte contains water and potassium polyphosphate dissolved in a concentration of 2.0 mol or more per 1 kg of the water.

[0011] <Option 4>

[0012] The aqueous battery according to claim 2 or 3, wherein the aqueous electrolyte contains water and potassium pyrophosphate as the potassium polyphosphate dissolved in the water.

[0013] <Option 5>

[0014] The aqueous battery according to any one of aspects 2 to 4, wherein the pH of the aqueous electrolyte is 3 or more and 13 or less.

[0015] The positive electrode active material of the present disclosure can be used as a positive electrode active material of an aqueous battery having an aqueous electrolyte containing potassium polyphosphate. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Hereinafter, features, advantages, and technical and industrial significance of exemplary embodiments of the present invention will be described with reference to the accompanying drawings, in which like reference numerals represent like elements, and in which:

[0017] Figure 1 An example of the structure of an aqueous battery is schematically shown.

[0018] Figure 2 X-ray diffraction patterns of the positive electrode active materials according to Examples and Comparative Examples are shown.

[0019] Figure 3 Discharge curves of the batteries according to Examples and Comparative Examples are shown.

[0020] Figure 4 The relationship between the potassium pyrophosphate concentration in the aqueous electrolyte and the ion conductivity of the aqueous electrolyte is shown.

[0021] Figure 5 The relationship between the potassium pyrophosphate concentration in the aqueous electrolyte and the pH of the aqueous electrolyte is shown. DETAILED DESCRIPTION

[0022] 1. Positive active material

[0023] There are few reports of inorganic compounds that can function as active materials in non-strongly alkaline aqueous electrolytes containing potassium ions. There are also few insights into what kind of inorganic compounds can be used as active materials, and the current situation is to confirm the activity of multiple inorganic compounds one by one. In particular, research on aqueous batteries using aqueous electrolytes containing potassium polyphosphate is still on the road to development, and there are even fewer reports of active materials. In this regard, there is a need for new positive electrode active materials that can be used in aqueous batteries with aqueous electrolytes containing potassium polyphosphate. For example, with respect to positive electrode active materials for aqueous batteries with aqueous electrolytes containing potassium polyphosphate, there is room for improvement in discharge capacity. The inventors have explored new materials that function as positive electrode active materials for aqueous batteries with aqueous electrolytes containing potassium polyphosphate, and found that the composite oxide disclosed below has a high discharge capacity as a positive electrode active material for aqueous batteries with aqueous electrolytes containing potassium polyphosphate.

[0024] The positive electrode active material disclosed herein has a monoclinic crystal structure belonging to the space group C2 / m and has a composition formula:x Mn 1-y Bi y O2·zH2O (A: one or both of Na and K, 0<x<1, 0<y<1, 0<z<2), and is used for an aqueous battery having an aqueous electrolyte containing water and potassium polyphosphate dissolved in the water. The positive electrode active material disclosed in the present invention has such a crystal structure and composition, so that ions contained in the aqueous electrolyte can be absorbed and released as charge compensation ions.

[0025] 1.1 Crystal structure

[0026] The positive active material disclosed herein has a monoclinic crystal structure belonging to the space group C2 / m. The positive active material disclosed herein may have diffraction peaks at least at 2θ=12.2°±0.5° and 24.5°±1.0° in an X-ray diffraction pattern using CuKα as a ray source, for example. The position of the diffraction peak may vary depending on the molar ratio of Mn and Bi constituting the positive active material.

[0027] In terms of the positive electrode active material disclosed in the present invention, on the one hand, it can also be said that Bi exists in the crystal structure of the layered manganese oxide having a monoclinic crystal structure. It is believed that by causing Bi to exist in the crystal structure of the layered manganese oxide having a monoclinic crystal structure, the crystal structure is stabilized and / or the electronic state in the crystal changes. Thus, it is believed that the charge compensation ions easily enter the interlayer of the crystal structure, and the discharge capacity as the positive electrode active material increases.

[0028] 1.2 Composition

[0029] The positive electrode active material disclosed in the present invention has a composition formula: x Mn 1-y Bi yA composition represented by O2·zH2O. Wherein A is one or both of Na and K. In the positive electrode active material disclosed in the present invention, even in the case of containing Na as A, even in the case of containing K as A ions, charge compensation ions can be inserted and extracted. x is greater than 0, and may be greater than 0.01, greater than 0.02, greater than 0.03, greater than 0.04, or greater than 0.05, and is less than 1, and may be less than 0.75, less than 0.50, less than 0.25, less than 0.20, less than 0.15, less than 0.10, less than 0.09, less than 0.08, less than 0.07, less than 0.06, or less than 0.05. y is greater than 0, and may be 0.01 or more, 0.02 or more, 0.03 or more, or 0.04 or more. It is less than 1 and may be 0.75 or less, 0.50 or less, 0.25 or less, 0.20 or less, 0.15 or less, 0.10 or less, 0.09 or less, 0.08 or less, 0.07 or less, 0.06 or less, 0.05 or less, or 0.04 or less. z is greater than 0, and may be 0.2 or more, 0.4 or more, 0.8 or more, 1.0 or more, 1.2 or more, 1.4 or more, 1.6 or more, or 1.8 or more. It is less than 2 and may be 1.8 or less, 1.6 or less, 1.4 or less, 1.2 or less, 1.0 or less, 0.8 or less, 0.4 or less, or 0.2 or less.

[0030] 1.3 Supplementary information on element configuration in crystal structure

[0031] The element configuration of the positive active material of the present disclosure only needs to have the above-mentioned composition and the above-mentioned crystal structure. In the positive active material of the present disclosure, A and H2O may exist in the interlayer composed of Mn-O octahedrons, for example. In addition, in the positive active material of the present disclosure, Bi may exist in the space of the above-mentioned crystal structure, for example. Alternatively, for example, in the Mn site of the positive active material of the present disclosure (Mn site of monoclinic layered manganese oxide), a portion of Mn may be replaced by Bi.

[0032] 1.4 Shape

[0033] The shape of the positive electrode active material disclosed in the present invention can be any shape that is generally used as a positive electrode active material for a battery. The positive electrode active material disclosed in the present invention can be, for example, in the form of particles. There is no particular limitation on the particle size in this case, and an appropriate size can be selected according to the design of the battery. The positive electrode active material disclosed in the present invention can be a primary particle or a secondary particle in which multiple primary particles are aggregated. The average particle size D50 of the positive electrode active material disclosed in the present invention can be, for example, greater than 1 nm and less than 1000 μm, and the lower limit can be greater than 5 nm or greater than 10 nm. In addition, the upper limit can be less than 500 μm, less than 100 μm, less than 50 μm, or less than 30 μm. It should be noted that the average particle size D50 referred to in this application is the particle size (median diameter) at the cumulative value of 50% in the volume-based particle size distribution obtained by laser diffraction scattering method.

[0034] 2. Method for producing positive electrode active material

[0035] As in the positive electrode active material of the present invention, for a composite oxide having a crystal structure belonging to the space group C2 / m and containing Mn and Bi, for example, after mixing and calcining the raw materials to obtain a predetermined precursor, the precursor can be subjected to post-treatment (soft chemical method) to synthesize. For example, the method for manufacturing the positive electrode active material of the present invention may include: mixing one or both of a Na source and a K source, a Mn source, and a Bi source to obtain a mixture; calcining the mixture to obtain a precursor; and obtaining the positive electrode active material by subjecting the precursor to an acid treatment.

[0036] 2.1 Mixing

[0037] The mixing of the Na source and / or K source, the Mn source, and the Bi source can be implemented by a known mixing means such as a ball mill. The mixing can be dry mixing or wet mixing using a dispersion medium or the like. The Na source can be, for example, sodium carbonate. The K source can be, for example, potassium carbonate. The Mn source can be, for example, manganese oxide. The Bi source can be, for example, bismuth oxide. A compound can serve as two or more of the Na source, the K source, the Mn source, and the Bi source. In the manufacturing method disclosed herein, for example, the Na source and / or K source, the Mn source, and the Bi source can be mixed in a specified ratio in such a way that the crystal structure of the precursor after sintering becomes an α-NaMnO2 type crystal structure.

[0038] 2.2 Firing

[0039] The calcination of the mixture can be carried out by a known calcination means such as a calcination furnace. The calcination atmosphere of the mixture can be, for example, an inert gas atmosphere such as nitrogen, or an oxygen-containing atmosphere. The heating rate from the calcination start temperature (for example, room temperature) to the calcination temperature can be, for example, 50°C / h or more and 500°C / h or less. The calcination temperature can be, for example, 700°C or more and 800°C or less. The calcination time can be, for example, 5 hours or more and 100 hours or less.

[0040] 2.3 Acid treatment

[0041] By subjecting the precursor obtained as described above to acid treatment, a positive electrode active material having a desired crystal structure and composition is obtained. The acid treatment can be implemented by contacting the above-mentioned precursor with various acid solutions. The acid constituting the acid solution may be an inorganic acid or an organic acid, and an inorganic acid is particularly preferably used. The inorganic acid may be, for example, sulfuric acid. The concentration and temperature of the acid solution can be any concentration and temperature that allow for appropriate acid treatment. The time of the acid treatment (contact time between the precursor and the acid solution) may be, for example, more than 5 hours and less than 100 hours. After the acid treatment, water washing and drying may be optionally performed.

[0042] 3. Aqueous batteries

[0043] like Figure 1 As shown, an aqueous battery 100 according to one embodiment includes a positive electrode active material layer 11, an aqueous electrolyte 20, and a negative electrode active material layer 31. The positive electrode active material layer 11 includes the positive electrode active material disclosed herein, that is, having a monoclinic crystal structure belonging to the space group C2 / m and having a composition formula: x Mn 1-y Bi y The positive electrode active material has a composition represented by O2·zH2O (A: one or both of Na and K, 0<x<1, 0<y<1, 0<z<2). The aqueous electrolyte 20 includes water and potassium polyphosphate dissolved in the water.

[0044] 3.1 Positive electrode active material layer

[0045] The positive electrode active material layer 11 contains the positive electrode active material of the present disclosure. In addition, the positive electrode active material layer 11 can be immersed in the aqueous electrolyte 20. In addition, the positive electrode active material layer 11 can contain a conductive auxiliary agent, a binder, various additives, etc. in addition to the positive electrode active material. The content of each component in the positive electrode active material layer 11 can be appropriately determined according to the target battery performance. There is no particular limitation on the shape of the positive electrode active material layer 11, for example, it can be a sheet-shaped positive electrode active material layer with a substantially flat surface.

[0046] 3.1.1 Positive electrode active material

[0047] The positive electrode active material layer 11 may contain only the positive electrode active material of the present disclosure as the positive electrode active material. Alternatively, the positive electrode active material layer 11 may contain the positive electrode active material of the present disclosure and other positive electrode active materials. Based on the total amount of positive electrode active materials contained in the positive electrode active material layer 11 (100% by mass), the positive electrode active material of the present disclosure may account for more than 0% by mass and less than 100% by mass, more than 10% by mass and less than 100% by mass, more than 30% by mass and less than 100% by mass, or more than 50% by mass and less than 100% by mass. Other positive electrode active materials may contain K element. Specifically, oxides, polyanions, etc. containing K element may be listed. More specifically, it may be a composite oxide of potassium and various transition metals. Furthermore, even when the K site in the composite oxide is composed of other alkali metal elements, various ions contained in the aqueous electrolyte 20 can be embedded and de-embedded. Alternatively, other positive electrode active materials may be Prussian blue, etc. Alternatively, other positive electrode active materials may be at least one selected from potassium titanate, TiO2, sulfur (S), etc., which has a potential that shows a higher charge and discharge potential than the negative electrode active material described later. Other positive electrode active materials may be, for example, in particulate form. Other positive electrode active materials may be primary particles or secondary particles in which multiple primary particles are aggregated. The average particle size D50 of other positive electrode active materials may be, for example, greater than 1 nm and less than 1000 μm, the lower limit may be greater than 5 nm or greater than 10 nm, and the upper limit may be less than 500 μm, less than 100 μm, less than 50 μm, or less than 30 μm.

[0048] 3.1.2 Conductive additives

[0049] As the conductive aid that can be contained in the positive electrode active material layer 11, for example, carbon materials such as vapor grown carbon fiber (VGCF), acetylene black (AB), Ketjen black (KB), carbon nanotubes (CNT), and carbon nanofibers (CNF); metal materials that are difficult to dissolve in aqueous electrolytes such as nickel, titanium, aluminum, and stainless steel can be listed. The conductive aid can be, for example, in the form of particles or fibers, and there is no particular limitation on the size. The conductive aid can be used alone or in combination of two or more.

[0050] 3.1.3 Adhesives

[0051] Examples of the binder that may be contained in the positive electrode active material layer 11 include butadiene rubber (BR) based binders, butylene rubber (IIR) based binders, acrylate butadiene rubber (ABR) based binders, styrene butadiene rubber (SBR) based binders, polyvinylidene fluoride (PVdF) based binders, polytetrafluoroethylene (PTFE) based binders, polyimide (PI) based binders, and the like. The binder may be used alone or in combination of two or more.

[0052] 3.2 Positive electrode collector

[0053] like Figure 1 As shown in the example, the positive electrode 10 of the aqueous battery 100 may include a positive electrode collector 12 in contact with the above-mentioned positive electrode active material layer 11. The positive electrode collector 12 may be in contact with the aqueous electrolyte 20. As for the positive electrode collector 12, any positive electrode collector that can function as a positive electrode collector of an aqueous battery can be used. The positive electrode collector 12 may be in the form of a foil, a plate, a mesh, a punched metal, a foam, etc. The positive electrode collector 12 may be composed of a metal foil or a metal mesh. In particular, the metal foil has excellent handling properties. The positive electrode collector 12 may be composed of a plurality of foils. As a metal material constituting the positive electrode collector 12, for example, a material containing at least one element selected from Cu, Ni, Al, V, Au, Pt, Mg, Fe, Ti, Pb, Co, Cr, Zn, Ge, In, Sn, and Zr can be listed. The positive electrode current collector 12 may be formed by plating or vapor-depositing the above-mentioned metal on a metal foil or a substrate. In addition, when the positive electrode current collector 12 is composed of a plurality of metal foils, there may be some layers between the plurality of metal foils. The thickness of the positive electrode current collector 12 is not particularly limited. For example, it may be 0.1 μm or more or 1 μm or less, and may be 1 mm or less or 100 μm or less.

[0054] 3.3 Aqueous electrolyte

[0055] The aqueous electrolyte 20 includes water and an electrolyte dissolved in the water. The aqueous electrolyte 20 may be in contact with the positive electrode current collector 12, or may be contained in the positive electrode active material layer 11, or may be in contact with the negative electrode current collector 32 described later, or may be contained in the negative electrode active material layer 31 described later, or may be retained by the separator 40 between the positive electrode active material layer 11 and the negative electrode active material layer 31.

[0056] 3.3.1 Solvent

[0057] The aqueous electrolyte 20 contains water as a solvent. The solvent contains water as a main component. That is, based on the total amount of the solvent constituting the aqueous electrolyte (100 mol%), water accounts for more than 50 mol% and less than 100 mol%. Water may account for more than 70 mol%, more than 90 mol% or more than 95 mol% of the total amount of the solvent. On the other hand, there is no particular upper limit on the proportion of water in the solvent. The solvent may contain only water (100 mol%). From the perspective of forming SEI (Sol id Electrolyte Interphase) on the surface of the active material, the aqueous electrolyte 20 may contain solvents other than water in addition to water. As solvents other than water, for example, one or more organic solvents selected from ethers, carbonates, nitriles, alcohols, ketones, amines, amides, sulfur compounds and hydrocarbons can be listed. The solvent other than water may account for 50 mol % or less, 30 mol % or less, 10 mol % or less, or 5 mol % or less, based on the total amount of the solvent constituting the aqueous electrolyte solution 20 (100 mol %).

[0058] 3.3.2 Electrolytes

[0059] At least potassium polyphosphate can be dissolved as an electrolyte in the aqueous electrolyte 20. The electrolyte can be dissociated into cations and anions in the aqueous electrolyte 20. In the aqueous electrolyte 20, cations can be completely dissociated from anions, or can be close to anions to form an association. For example, potassium ions contained in the aqueous electrolyte can also form an association with anions. The aqueous electrolyte 20 can contain multiple cations. For example, the aqueous electrolyte 20 contains potassium ions, and can contain other cations while containing the potassium ions. For example, alkali metal ions, alkaline earth metal ions, transition metal ions, etc. other than potassium ions can be contained. In addition, the aqueous electrolyte 20 naturally contains protons. In addition, the aqueous electrolyte 20 can also contain more than one anion. For example, the aqueous electrolyte 20 contains polyphosphate anions. There is no particular limitation on the type of anions other than polyphosphate anions. The aqueous electrolyte 20 naturally contains hydroxide ions. As described above, the aqueous electrolyte 20 contains protons and hydroxide ions in addition to cations and anions from potassium polyphosphate, and at least one of these ions can be a carrier ion. In the present embodiment, the carrier ion can be a proton, a hydroxide ion, a cation from potassium polyphosphate, an anion from potassium polyphosphate, or a combination thereof. There is no particular limitation on the concentration of the electrolyte in the aqueous electrolyte 20. The concentration of the electrolyte in the aqueous electrolyte 20 can be adjusted according to the target performance. According to the knowledge of the inventors, the higher the concentration of the electrolyte in the aqueous electrolyte 20, the easier it is to expand the potential window of the aqueous electrolyte 20. In addition, the higher the concentration, the easier it is for the capacity of the aqueous battery 100 to become larger. Furthermore, the higher the concentration, the easier it is to suppress the dissolution of the collector in the aqueous electrolyte 20. On the other hand, the lower the concentration, the easier it is for the viscosity of the aqueous electrolyte 20 to become smaller.

[0060] The aqueous electrolyte 20 may contain various potassium compounds soluble in water as electrolytes in addition to potassium polyphosphate. Such electrolytes include at least one of KPF6, KBF4, K2SO4, KNO3, CH3COOK, (CF3SO2)2NK, KCF3SO3, (FSO2)2NK, K2HPO4, KH2PO4, and KPO3.

[0061] According to the findings of the present inventors, when the aqueous electrolyte 20 includes water and potassium phosphate or acetate dissolved in the water, and in particular, when it includes water and potassium phosphate dissolved in the water, and in particular, when it includes water and potassium polyphosphate dissolved in the water, the performance of the aqueous battery 100 is easily improved. The so-called "potassium polyphosphate" refers to a salt in which at least a portion of the hydrogen in polyphosphoric acid is replaced by potassium. That is, "potassium polyphosphate" is a concept that includes potassium hydrogen polyphosphate. Specific examples of potassium polyphosphate include potassium pyrophosphate (K4-x H x P2O7), potassium tripolyphosphate (K 5-x H x P3O 10 )、Potassium tetrapolyphosphate( K6-x H x P4O 13 ), potassium heptapolyphosphate (K 7-x H x P5O 16 ) etc. Among them, when potassium pyrophosphate (K 4-x H x P2O7) as potassium polyphosphate, it is easy to ensure higher performance. That is, the aqueous electrolyte 20 involved in one embodiment may include water and potassium pyrophosphate as the potassium polyphosphate dissolved in the water. The aqueous electrolyte 20 may also include other electrolytes as electrolytes while containing potassium pyrophosphate. In this case, based on the total amount of electrolytes dissolved in the aqueous electrolyte 20 (100 mol%), potassium polyphosphate may account for more than 50 mol% and less than 100 mol%, more than 70 mol% and less than 100 mol%, or more than 90 mol% and less than 100 mol%, and other electrolytes may account for more than 0 mol% and less than 50 mol%, more than 0 mol% and less than 30 mol%, or more than 0 mol% and less than 10 mol%.

[0062] The "potassium polyphosphate dissolved in water" in the aqueous electrolyte 20 can be dissociated into potassium ions and anions. In the aqueous electrolyte 20, potassium ions can be completely dissociated from anions, or can be close to anions to form an association. For example, when the aqueous electrolyte 20 contains potassium pyrophosphate dissolved in water, the "potassium pyrophosphate dissolved in water" in the aqueous electrolyte 20 can be K + 、P2O7 4- 、KP2O7 3- 、K2P2O7 2- 、K3P2O7 - Such ions, their associations, and the ability to extract H from H2O + As HP2O7 3- 、H2P2O7 2- 、H3P2O7 - Existence or H + With K + Associating as HK2P2O7 - 、HKP2O7 2- 、H2KP2O7 -In the aqueous electrolyte 20, the "concentration of potassium polyphosphate dissolved in water" is determined by converting the ions, aggregates, etc. contained in the aqueous electrolyte 20 into potassium pyrophosphate. In addition, when the aqueous electrolyte 20 contains polyphosphate ions (pyrophosphate ions, as described above, in addition to P2O7 4- In addition, KP2O7 3- 、K2P2O7 2- 、K3P2O7 - 、HP2O7 3- 、H2P2O7 2- 、H3P2O7 - 、HK2P2O7 - 、HKP2O7 2- 、H2KP2O7 - In the case where the polyphosphate ions contained in the aqueous electrolyte 20 are used as anions (such as those existing in a state of being combined with cations), all of the polyphosphate ions contained in the aqueous electrolyte 20 may not be converted into "dissolved potassium polyphosphate". That is, the aqueous electrolyte 20 may contain polyphosphate ions at a concentration higher than that which can be converted into potassium polyphosphate. For example, when the aqueous electrolyte 20 is manufactured, when a pyrophosphate ion source other than K4P2O7 (such as H4P2O7, etc.) is added to water and dissolved, the aqueous electrolyte 20 contains pyrophosphate ions at a concentration higher than that which can be converted into potassium pyrophosphate. On the other hand, in the aqueous electrolyte 20, when a potassium ion source other than potassium salt (such as KOH) and an anion source other than potassium salt (such as H4P2O7) are dissolved in water respectively and dissociated into potassium ions and anions, the potassium ions and anions are converted into "potassium salt dissolved in water". For example, when KOH and H4P2O7 are dissolved in the aqueous electrolyte 20, they can be converted into potassium pyrophosphate.

[0063] The aqueous electrolyte 20 may include water and potassium polyphosphate dissolved at a concentration of more than a certain value relative to 1 kg of the water. The concentration of potassium polyphosphate relative to 1 kg of water may be, for example, more than 2.0 mol, more than 2.5 mol, more than 3.0 mol, more than 3.5 mol, or more than 4.0 mol. There is no particular upper limit on the concentration of potassium polyphosphate in the aqueous electrolyte 20. If the concentration is too high, the viscosity of the aqueous electrolyte 20 may increase excessively. In this regard, the concentration of potassium polyphosphate relative to 1 kg of water may be less than 8.0 mol, less than 7.0 mol, or less than 6.0 mol. When the concentration of potassium polyphosphate relative to 1 kg of water is more than 2.0 mol, the redox resistance unique to the so-called concentrated aqueous solution of Water-in-salt is manifested, making it a more preferred aqueous electrolyte as an aqueous electrolyte. In addition, various physical properties described later can be ensured.

[0064] 3.3.3 Other ingredients

[0065] The aqueous electrolyte 20 may contain, in addition to the above-mentioned solvent and electrolyte, an acid, a hydroxide, etc. for adjusting the pH of the aqueous electrolyte 20. In addition, various additives may be contained.

[0066] 3.3.4 Physical properties of aqueous electrolytes

[0067] (1) The pH of the aqueous electrolyte 20 is not particularly limited. However, if the pH is too high, the oxidation side potential window of the aqueous electrolyte may be narrowed. In this regard, the pH of the aqueous electrolyte may be 3 or more and 13 or less. The pH may be 4 or more, 5 or more, 6 or more, 7 or more, 8 or more, 9 or more, or 10 or more, and may be 12 or less.

[0068] (2) The aqueous electrolyte 20 may not have a freezing point above -60°C. Among them, the presence or absence of the "freezing point" of the aqueous electrolyte 20 is confirmed by differential scanning calorimetry (DSC). As for the scanning speed according to DSC, both the cooling and heating are set to 5°C / min, and the scanning range is set to cool from room temperature to -120°C and then heat up to 40°C. In addition, the atmosphere in DSC is set to an inert gas atmosphere such as Ar, and the pressure is the same as the atmospheric pressure. However, a sealed aluminum container is used in the evaluation, so the atmosphere in the container becomes an atmosphere sealed under atmospheric pressure. For the aqueous electrolyte, the measurement is carried out under the above conditions. If the crystallization peak temperature (freezing point temperature) is not confirmed above -60°C, the aqueous electrolyte is regarded as "not having a freezing point above -60°C". In the aqueous battery 100 of the present disclosure, in order to achieve the condition that "the aqueous electrolyte 20 has no freezing point at -60°C or higher", it is effective to make the concentration of the electrolyte in the aqueous electrolyte 20 high. When the aqueous electrolyte 20 does not have a freezing point at -60°C, the number of free water molecules in the aqueous electrolyte 20 decreases, and the metal contained in the current collector becomes difficult to dissolve into the aqueous electrolyte 20. In addition, since the aqueous electrolyte 20 does not have a freezing point at -60°C, the aqueous battery 100 can be used even at extremely low temperatures. That is, the aqueous battery 100 operates appropriately even in cold regions.

[0069] (3) When the aqueous electrolyte 20 is cooled from 0°C to -60°C, it is preferably not accompanied by salt precipitation. In this way, the aqueous electrolyte 20 is not accompanied by salt precipitation due to temperature changes, so that ion conduction can be stably performed even at low temperatures. For example, the aqueous battery 100 can be used even at extremely low temperatures such as in cold regions. As described above, the aqueous electrolyte 20 contains water and potassium polyphosphate dissolved in the water. According to the findings of the present inventors, the temperature dependence of the saturated solubility of potassium polyphosphate on water is small and hardly changes at low temperatures below 0°C. In this regard, potassium polyphosphate is dissolved at a high concentration in the aqueous electrolyte 20 at 0°C, and even if the aqueous electrolyte 20 is cooled from 0°C to -60°C, there is basically no precipitation of potassium polyphosphate in the aqueous electrolyte 20.

[0070] (4) If the viscosity of the aqueous electrolyte 20 is too high, the ion conductivity of the aqueous electrolyte 20 may be reduced. On the other hand, when the electrolyte is dissolved in the aqueous electrolyte 20 at a high concentration, the aqueous electrolyte 20 may have a viscosity above a certain level. The aqueous electrolyte 20 may have a viscosity of 10 mPa·s or more and 600 mPa·s or less at 20°C.

[0071] 3.4 Negative electrode active material layer

[0072] The negative electrode active material layer 31 contains a negative electrode active material. In addition, the negative electrode active material layer 31 may contain a conductive aid, a binder, various additives, etc. in addition to the negative electrode active material. In addition, the negative electrode active material layer 31 may be immersed in an aqueous electrolyte 20. The content of each component in the negative electrode active material layer 31 can be appropriately determined according to the target battery performance. For example, the entire negative electrode active material layer 31 (the entire solid component) is set to 100 mass%, and the content of the negative electrode active material can be more than 40 mass%, can be less than 100 mass% or less than 90 mass%. There is no particular limitation on the shape of the negative electrode active material layer 31, for example, it can be a sheet-shaped negative electrode active material layer with a roughly flat surface.

[0073] 3.4.1 Negative electrode active material

[0074] As for the negative electrode active material, a negative electrode active material known as a negative electrode active material for aqueous batteries can be used. The negative electrode active material may, for example, include at least one selected from potassium-transition metal composite oxides; titanium oxide; metal sulfides such as Mo6S8; elemental sulfur; KTi2(PO4)3; NASICON-type compounds; WO3, etc. Alternatively, the negative electrode active material may also be a hydrogen storage alloy. Alternatively, the negative electrode active material may be an inorganic compound having a crystal structure belonging to the space group I23. The inorganic compound having a crystal structure belonging to the space group I23 may, for example, include element A, element M and O. Among them, the element A is at least one of Bi and La, the element M is at least one of Bi, Mn, Fe, Co and Ni, and both element A and element M may be Bi. The negative electrode active material can embed and deintercalate ions by intercalation, and can also embed and deintercalate carriers by conversion reactions, alloying reactions, etc. The negative electrode active material can be used alone or in combination of two or more. The shape of the negative electrode active material can be any shape that can function as the negative electrode active material of the battery. The negative electrode active material can be, for example, in the form of particles. The negative electrode active material can be a primary particle or a secondary particle in which a plurality of primary particles are aggregated. The average particle size D50 of the negative electrode active material can be, for example, greater than 1 nm and less than 1000 μm, the lower limit can be greater than 5 nm or greater than 10 nm, and the upper limit can be less than 500 μm, less than 100 μm, less than 50 μm, or less than 30 μm.

[0075] 3.4.2 Other ingredients

[0076] The conductive aid and binder that may be contained in the negative electrode active material layer 31 may be appropriately selected from the conductive aids and binders exemplified as the conductive aids and binders that may be contained in the positive electrode active material layer 11. The conductive aid and binder may be used alone or in combination of two or more.

[0077] 3.5 Negative electrode collector

[0078] like Figure 1As shown, the negative electrode 30 of the aqueous battery 100 may include a negative electrode collector 32 in contact with the above-mentioned negative electrode active material layer 31. The negative electrode collector 32 may be in contact with the aqueous electrolyte 20. As for the negative electrode collector 32, any negative electrode collector that can function as a negative electrode collector of an aqueous battery can be used. The negative electrode collector 32 may be in the form of a foil, a plate, a mesh, a punched metal, and a foam. The negative electrode collector 32 may be composed of a metal foil or a metal mesh. In particular, the metal foil has excellent handling properties. The negative electrode collector 32 may be composed of a plurality of foils. As a metal material constituting the negative electrode collector 32, for example, a metal material containing at least one element selected from Cu, Ni, Al, V, Au, Pt, Mg, Fe, Ti, Pb, Co, Cr, Zn, Ge, In, Sn, and Zr can be cited. In particular, the negative electrode collector 32 containing at least one selected from Al, Ti, Pb, Zn, Sn, Mg, Zr and In, and in particular the negative electrode collector 32 containing Al, has high performance. Al, Ti, Pb, Zn, Sn, Mg, Zr and In all have low work functions, and it is believed that even if the negative electrode collector 32 contacts the aqueous electrolyte 20 at a reduction potential, it is difficult for the aqueous electrolyte 20 to be electrolyzed. The negative electrode collector 32 may be formed by plating or vapor-depositing the above-mentioned metal on a metal foil or a substrate. In addition, when the negative electrode collector 32 is composed of a plurality of metal foils, there may be some layers between the plurality of metal foils. The thickness of the negative electrode collector 32 is not particularly limited. For example, it may be 0.1 μm or more or 1 μm or more, and may be 1 mm or less or 100 μm or less.

[0079] 3.6 Other components

[0080] In addition to the basic structure described above, the aqueous battery 100 may include the following other structures, for example. As described above, in the aqueous battery 100, a separator 40 may exist between the positive electrode active material layer 11 and the negative electrode active material layer 31. The separator 40 may adopt the separator used in aqueous electrolyte batteries (nickel-hydrogen batteries, zinc-air batteries, etc.). For example, it may be a hydrophilic separator such as a non-woven fabric made of cellulose. There is no particular limitation on the thickness of the separator 40, for example, it may be greater than 5μm and less than 1mm. In addition to the above-mentioned structure, the aqueous battery 100 may include terminals, battery casings, etc. The aqueous battery 100 may be a secondary battery.

[0081] 4. Method for manufacturing aqueous batteries

[0082] The aqueous battery 100 of the present disclosure can be manufactured, for example, as follows.

[0083] (1) The positive electrode active material constituting the positive electrode active material layer 11 is dispersed in a solvent to obtain a positive electrode mixture paste (slurry). As the solvent used in this case, water or various organic solvents can be used. The positive electrode mixture paste (slurry) is applied to the surface of the positive electrode collector 12 using a scraper or the like, and then dried to form the positive electrode active material layer 11 on the surface of the positive electrode collector 12 to obtain the positive electrode 10. As a coating method, in addition to the scraper method, an electrostatic coating method, a dip coating method, a spray coating method, etc. can also be used.

[0084] (2) The aqueous electrolyte solution 20 can be produced, for example, by mixing water and an electrolyte. The aqueous electrolyte solution 20 can also be obtained by simply filling a container with water and an electrolyte and leaving them there to mix them.

[0085] (3) The negative electrode active material constituting the negative electrode active material layer 31 is dispersed in a solvent to obtain a negative electrode mixture paste (slurry). As the solvent used in this case, water or various organic solvents can be used. The negative electrode mixture paste (slurry) is applied to the surface of the negative electrode collector 32 using a scraper or the like, and then dried to form a negative electrode active material layer 31 on the surface of the negative electrode collector 32 to obtain a negative electrode 30. As a coating method, in addition to the scraper method, an electrostatic coating method, a dip coating method, a spray coating method, etc. can also be used.

[0086] (4) The aqueous battery 100 is obtained by placing the positive electrode 10, the aqueous electrolyte 20 and the negative electrode 30 in a battery case. For example, the separator 40 is sandwiched between the positive electrode 10 and the negative electrode 30 to obtain a stack having the positive electrode collector 12, the positive electrode active material layer 11, the separator 40, the negative electrode active material layer 31 and the negative electrode collector 32 in sequence. In the stack, other components such as terminals are installed as needed. The stack is placed in a battery case, and the aqueous electrolyte 20 is filled in the battery case, so that the stack is immersed in the aqueous electrolyte 20, and the stack and the electrolyte are sealed in the battery case, so that the aqueous battery 100 can be obtained.

[0087] The technology of the present disclosure will be described in more detail below using Examples and Comparative Examples, but the technology of the present disclosure is not limited to these.

[0088] 1. Preparation of positive electrode active material

[0089] 1.1 Example: Preparation of positive electrode active material using soft chemical method

[0090] 1.1.1 Synthesis of precursors

[0091] As the initial raw materials, sodium carbonate, manganese trioxide and bismuth trioxide were weighed in a molar ratio of 1:0.95:0.05, and a planetary ball mill was used to crush and mix for 2 hours to obtain a mixture. The obtained mixture was placed in an alumina crucible and placed in a sintering furnace. Nitrogen was flowed into the furnace. After deoxidation, the temperature was directly increased to 750°C at a heating rate of 150°C / h and maintained at 750°C for 60 hours to sinter the mixture. Then, it was slowly cooled to room temperature, and after stopping the flow of nitrogen, the precursor as the sintered product was recovered from the furnace. The X-ray diffraction pattern of the obtained precursor was confirmed, and the result showed that the precursor showed the same diffraction pattern as the single-phase α-NaMnO2, and it was judged that Bi entered the crystal structure.

[0092] 1.1.2 Acid treatment of precursor

[0093] The precursor obtained as described above was placed in a 300 ml beaker, 250 ml of sulfuric acid solution (sulfuric acid concentration: 0.3 mol / L) was added thereto, and stirred at 20°C for 24 hours. After the stirring was completed, suction filtration was performed using a Buchner funnel, and the mixture was washed with a BaCl2 aqueous solution until no white precipitate of BaSO4 was produced to obtain a wet cake. The obtained wet cake was dried in a warm air dryer at 50°C for 24 hours, and then classified using a standard sieve with a mesh size of 30 μm to obtain a positive electrode active material.

[0094] 1.1.3 Confirmation of crystal structure and composition

[0095] The obtained positive electrode active material was confirmed to have an X-ray diffraction pattern using CuKα as the radiation source. Figure 2 The X-ray diffraction pattern of the positive electrode active material involved in the embodiment is shown in FIG. Figure 2 As shown, it is confirmed that the positive electrode active material has a monoclinic layered crystal structure belonging to the space group C2 / m in a single phase. In addition, for the obtained positive electrode active material, elemental analysis was performed by IPC measurement, and it was confirmed that the composition ratio of Na relative to the total of Mn and Bi in the positive electrode active material Na / (Mn+Bi) was 0.05, the composition ratio of Bi relative to the total of Mn and Bi Bi / (Mn+Bi) was 0.04, and it contained 13.7% by mass of water. In other words, the positive electrode active material involved in the embodiment has a monoclinic crystal structure belonging to the space group C2 / m, and has a composition formula: Na 0.05 Mn 0.96 Bi 0.04 The composition represented by O2·0.83H2O.

[0096] 1.2 Comparative Example: Preparation of positive electrode active material using solution method

[0097] 1.2.1 Solution preparation

[0098] Ion exchange water was added to 19.8 g of manganese (II) chloride tetrahydrate to prepare 200 ml of a 0.5 mol / L manganese chloride aqueous solution. Separately, ion exchange water was added to 109 g of a 50 w / w% sodium hydroxide aqueous solution to prepare 250 ml of a 5.5 mol / L sodium hydroxide aqueous solution.

[0099] 1.2.2 Preparation of positive electrode active material using solution reaction

[0100] The above-mentioned manganese chloride aqueous solution is transferred to a 1L stirring container in which gas can flow, and then placed in a cooling bath, the temperature is cooled to below 10°C, and Ar gas is bubbled while stirring to drive out the air in the container. While maintaining the temperature and bubbling the gas and stirring, the above-prepared sodium hydroxide aqueous solution is added to the manganese chloride aqueous solution with a drum pump for 15 minutes and mixed to generate a turbid slurry. Then, the gas pipe is connected to the air pump, and air is sent in at 6L / min, and bubbling is continued for more than 20 hours to make the slurry black and promote the oxidation reaction. After the reaction is completed, it is filtered using a Buchner funnel, washed with AgNO3 aqueous solution to the extent that no white precipitate of AgCl is produced, and a wet cake is obtained. The obtained wet cake is dried for a day and night with a warm air dryer at 80°C, and then classified using a standard sieve with a mesh size of 38μm to obtain a positive electrode active material.

[0101] 1.2.3 Confirmation of crystal structure and composition

[0102] The obtained positive electrode active material was confirmed to have an X-ray diffraction pattern using CuKα as the radiation source. Figure 2 The X-ray diffraction pattern of the positive electrode active material involved in the comparative example is shown in FIG. Figure 2 As shown, it is confirmed that the positive electrode active material has a monoclinic layered crystal structure belonging to the space group C2 / m in a single phase. In addition, for the obtained positive electrode active material, elemental analysis was performed by IPC measurement, and it was confirmed that the composition ratio of Na to Mn in the positive electrode active material was 0.29, and it contained 10.9% by mass of water. In other words, the positive electrode active material involved in the comparative example has a monoclinic crystal structure belonging to the space group C2 / m, and has a composition formula: Na 0.29 The composition represented by MnO2·0.64H2O.

[0103] 2. Preparation of positive electrode

[0104] The positive electrode active material, acetylene black as a conductive aid, and PVdF as a binder were mixed with a solvent in a mass ratio of positive electrode active material: conductive aid: binder = 75:20:5 to prepare ink. The obtained ink was dropped onto the surface of Ti foil and then applied to a uniform film with a doctor blade to obtain a positive electrode having Ti foil and a positive electrode active material layer provided on the surface of the Ti foil.

[0105] 3. Preparation of aqueous electrolyte

[0106] 5 mol of K4P2O7 was dissolved in 1 kg of pure water to obtain an aqueous electrolyte for evaluation. The aqueous electrolyte had a pH of 3 or more and 13 or less, had no freezing point at -60°C or more, did not precipitate salts when cooled from 0°C to -60°C, and had a viscosity at 20°C of 10 mPa·s or more and 350 mPa·s or less.

[0107] 4. Preparation of battery cells for evaluation

[0108] An evaluation cell (VM4, EC Frontier) was prepared using the above-mentioned positive electrode as a working electrode, a Pt mesh as a counter electrode, Ag / AgCl as a reference electrode, and the above-mentioned aqueous electrolyte.

[0109] 5. Evaluation of battery cells

[0110] The battery cell for evaluation was charged and discharged under the following conditions to obtain a discharge curve.

[0111] Charge and discharge current value: 0.2mA / cm 2

[0112] Cut-off voltage: -0.5~0.85Vvs.Ag / AgCl

[0113] Measurement temperature: 25℃

[0114] 6. Evaluation results

[0115] exist Figure 3 Graphs showing the discharge curve of the battery according to the embodiment and the discharge curve of the battery according to the comparative example are shown in FIG. Figure 3As shown, it is known that the positive electrode active material involved in the embodiment can be charged and discharged in the aqueous electrolyte containing potassium polyphosphate, and compared with the positive electrode active material involved in the comparative example, it has a significantly high discharge capacity. It is believed that the positive electrode active material involved in the embodiment exists together with Mn in the monoclinic crystal structure belonging to the space group C2 / m, so that the crystal structure is stabilized, and / or the electronic state in the crystal changes. It is believed that thus, the charge compensation ions (such as potassium ions and / or protons) from the aqueous electrolyte easily enter the interlayer of the crystal structure, and the discharge capacity increases.

[0116] 7. Supplement

[0117] exist Figure 4 The relationship between the concentration of potassium pyrophosphate aqueous solution and ion conductivity is shown in FIG. Figure 4 As shown in FIG. 1 , when the concentration of potassium pyrophosphate in the potassium pyrophosphate aqueous solution is more than 0 mol / kg and less than 8 mol / kg, the potassium pyrophosphate aqueous solution has excellent ion conductivity. Figure 5 The relationship between the concentration and pH of the potassium pyrophosphate aqueous solution is shown in FIG. Figure 5 As shown, when the concentration of potassium pyrophosphate in the potassium pyrophosphate aqueous solution exceeds 0 mol / kg and is 8 mol / kg or less, the pH of the potassium pyrophosphate aqueous solution is 10.0 to 12.0.

[0118] It should be noted that in the above-mentioned embodiments, an evaluation battery cell having a predetermined aqueous electrolyte, a predetermined positive electrode as a working electrode, a Pt mesh as a counter electrode, and Ag / AgCl as a reference electrode was used to simply evaluate the performance of the active material contained in the positive electrode. However, the composition other than the positive electrode active material is not the essence of the technology disclosed in the present invention. In the case of actually constructing an aqueous battery, an aqueous electrolyte and a negative electrode may be used together with the predetermined positive electrode active material.

Claims

1. A positive electrode active material having a monoclinic crystal structure belonging to space group C2 / m and having a composition formula: A x Mn 1- y Bi y The composition represented by O2·zH2O, where A is one or both of Na and K, 0<x<1, 0<y<1, 0<z<2, and the positive electrode active material is used for an aqueous battery having an aqueous electrolyte containing water and potassium polyphosphate dissolved in the water.

2. An aqueous battery comprising a positive electrode active material layer, an aqueous electrolyte and a negative electrode active material layer, wherein the positive electrode active material layer comprises the positive electrode active material according to claim 1, and the aqueous electrolyte comprises water and potassium polyphosphate dissolved in the water.

3. The aqueous battery according to claim 2, wherein: The aqueous electrolyte solution includes water and potassium polyphosphate dissolved in a concentration of 2.0 mol or more per 1 kg of the water.

4. The aqueous battery according to claim 2, wherein: The aqueous electrolyte solution includes water and potassium pyrophosphate as the potassium polyphosphate dissolved in the water.

5. The aqueous battery according to any one of claims 2 to 4, wherein The pH of the aqueous electrolyte is 3 or more and 13 or less.